Pregnancy during deprivation of liberty: a mixed study (Research, Society and Development, 2020)
Objective: to highlight the process of being a pregnant woman deprived of liberty. Method: cross-sectional study conducted in 2019 in a state penitentiary located in a border area in the western region of Rio Grande do Sul State / Brazil. For data collection, the semi-structured interview technique was applied. Data analysis was based on the mixed approach that allows the combination of qualitative and quantitative data. Results: of the 32 women prisoners, eight met the inclusion criteria, because they were pregnant in a prison environment. There is an increase in the number of children of these pregnant women. Conclusion: pregnant women demand a differentiated health care, as this emphasizes the need to have a Basic Prison Health Unit in place and assistance to women both their reproductive health and family planning. Health professionals are responsible for strengthening women in their psycho-emotional aspects and guiding them during nursing consultations.